Winter distribution of Whooper Swans Cygnus cygnus ringed in four geographically discrete regions in Iceland between 1988 and 2006: an update - Newth, Julia; Colhoun, Kendrew; Einarsson, Olafur; McElwaine, Graham; Thorstensen, Sverrir; Hesketh, Richard; Petersen, Aevar; Wells, Jim; Rees, Eileen (Wildfowl, 2013)
Between 1988 and 2006, a total of 5,110 Whooper Swans Cygnus cygnuswere Between 1988 and 2006, a total of 5,110 Whooper Swans Cygnus cygnus were caught and marked with plastic leg-rings in four geographically discrete parts of Iceland. Of these, 53.6% were subsequently sighted at wintering sites, mainly in Britain and Ireland but with small numbers seen wintering in Iceland and elsewhere in Europe. Overall, the swans migrated on a broad front, had a predominantly northerly distribution in Britain and were widespread throughout many areas of Ireland, particularly in a belt stretching from the northeast to the southwest. Birds were distributed rather more evenly throughout Scotland. In England/Wales they were concentrated at relatively few sites, notably the Ouse Washes, Norfolk and Martin Mere/Ribble Estuary, Lancashire. Birds ringed in the more western parts of Iceland (in Skagafjörur) concentrated largely in more western parts of the wintering range (Ireland), whereas those ringed in east Iceland (NorurMúlasy´sla) were more likely to occur in Scotland and in continental Europe. An overall southerly shift in distribution as the winter progressed was also detected.